2013
DOI: 10.1371/journal.pone.0069359
|View full text |Cite
|
Sign up to set email alerts
|

Human Ubc9 Is Involved in Intracellular HIV-1 Env Stability after Trafficking out of the Trans-Golgi Network in a Gag Dependent Manner

Abstract: The cellular E2 Sumo conjugase, Ubc9 interacts with HIV-1 Gag, and is important for the assembly of infectious HIV-1 virions. In the previous study we demonstrated that in the absence of Ubc9, a defect in virion assembly was associated with decreased levels of mature intracellular Envelope (Env) that affected Env incorporation into virions and virion infectivity. We have further characterized the effect of Ubc9 knockdown on HIV Env processing and assembly. We found that gp160 stability in the endoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Several studies have reported that UBE2I interacts with HIV-1 viral proteins and plays an important role in viral replication [ 66 ]. The knockdown of endogenous UBE2I expression in HIV-1 infected cells caused defects in the trafficking of HIV-1 gag and env proteins resulting in the production of defective virus particles that were not infectious [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that UBE2I interacts with HIV-1 viral proteins and plays an important role in viral replication [ 66 ]. The knockdown of endogenous UBE2I expression in HIV-1 infected cells caused defects in the trafficking of HIV-1 gag and env proteins resulting in the production of defective virus particles that were not infectious [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of Ubc9 sumoylation at K14 , phosphorylation at S71 , and the recent identification of hypoxia‐mediated downregulation of Ubc9 K65 acetylation might provide interesting clues on the impact of these functional states on Ubc9 half‐life. The relevance of Ubc9 protein stability comes from studies where depleting Ubc9 in cells that produce HIV Type I virions reduces infectivity by 8–10 fold . Perhaps for this reason, cancers of various histologic origins have been identified with elevated levels of Ubc9 particularly of the skin, prostate, lung, colon, and ER positive breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The Ubc9‐Gag interaction, which has been shown to be important for gp120 stability, also occurs with the catalytically dead Ubc9. Furthermore, compared to Ubc9 depleted cells, the catalytically dead Ubc9 mutant was unable to affect levels of viral infectivity .…”
Section: Introductionmentioning
confidence: 90%
“…In addition, some viral proteins such as the human cytomegalovirus (HCMV) IE1 protein [ 47 ] and the HPV E1 protein [ 48 ] can exploit the host sumoylation mechanism because they need to be SUMO-modified in order to exert their functions. Some other viral proteins such as human herpes virus-6 (HHV6) IE1, Epstein-Barr virus (EBV) Zta, EBV Rta, human immunodeficiency virus (HIV) P6 Gag, and the N protein of severe acute respiratory syndrome coronavirus (SARS-CoV) have all been shown to take advantage of the host sumoylation system [ 5 , 49 , 50 ]. In addition, some viruses encode sumoylation mimicking enzymes, such as the Kaposi’s sarcoma-associated herpes virus (KSHV) K-bZIP protein and the adenovirus early region 1B 55-kDa protein (E1B-55K) protein, both of which possess SUMO ligase activities [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%